Efficacy and safety of a pentavalent live human-bovine reassortant rotavirus vaccine (RV5) in healthy Chinese infants: A randomized, double-blind, placebo-controlled trial. Issue 43 (13th October 2017) - Mo, Zhaojun; Mo, Yi; Li, Mingqiang; Tao, Junhui; Yang, Xu; Kong, Jilian; Wei, Dingkai; Fu, Botao; Liao, Xueyan; Chu, Jianli; Qiu, Yuanzheng; Hille, Darcy A.; et al.
Highlights: A randomized, double-blind, placebo-controlled trial was conducted in healthy Chinese infants. Efficacy and safety of a pentavalent rotavirus vaccine (RV5) were assessed. Efficacy against rotavirus gastroenteritis of any-severity caused by any serotype was 69.3%. Efficacy against severe rotavirus gastroenteritis caused by any serotype was 78.9%. RV5 was efficacious and generally well-tolerated in Chinese infants. Abstract: Background: A randomized, double-blind, placebo-controlled multicenter trial was conducted in healthy Chinese infants to assess the efficacy and safety of a pentavalent live human-bovine reassortant rotavirus vaccine (RotaTeq™, RV5) against rotavirus gastroenteritis (RVGE). Methods: 4040 participants aged 6–12 weeks were enrolled and randomly assigned to either 3 oral doses of RV5 (n = 2020) or placebo (n = 2020), administered ∼4 weeks apart. The participants also received OPV and DTaP in a concomitant or staggered fashion. The primary objective was to evaluate vaccine efficacy (VE) against naturally-occurring RVGE at least 14 days following the third dose. Key secondary objectives included: VE against naturally-occurring severe RVGE and VE against severe and any-severity RVGE caused by rotavirus serotypes contained in the vaccine, occurring at least 14 days after the third dose. All adverse events (AEs) were collected for 30 days following each dose. Serious AEs (SAEs) and intussusception cases were collected during the entire study. (ClinicalTrials.gov registry: NCT02062385). Results: VE against RVGE of any-severity caused by any serotype was 69.3% (95% CI: 54.5, 79.7). The secondary efficacy analysis showed an efficacy of: 78.9% (95% CI: 59.1, 90.1) against severe RVGE caused by any serotype; 69.9% (95% CI: 55.2, 80.3) and 78.9% (95% CI: 59.1, 90.1) against any-severity and severe RVGE caused by serotypes contained in the vaccine, respectively. Within 30 days following any vaccination, 53.5% (1079/2015) and 53.3% (1077/2019) of participants reported at least one AE, and 5.8% (116/2015) and 5.7% (116/2019) reported SAEs in the vaccine and placebo groups, respectively. No SAEs were considered vaccine-related in recipients of RV5. Two intussusception cases were reported in recipients of RV5 who recovered after receiving treatment. Neither was considered vaccine-related. Conclusions: In Chinese infants, RV5 was efficacious against any-severity and severe RVGE caused by any serotype and generally well-tolerated with respect to AEs.